Effect of blue and red monochromatic light during incubation on the early post-embryonic development of immune responses in broiler chicken. Issue 4 (4th July 2022) - Kankova, Z.; Drozdova, A.; Hodova, V.; Zeman, M.
ABSTRACT: 1. The light regime during incubation can influence embryonic and post-embryonic life and its effects can be mediated by rhythmic melatonin production in the embryonic pineal gland. 2. This study explored whether the incubation of chick embryos under red or blue monochromatic light, which induces maximum and minimum melatonin production, respectively, can influence the development and reactivity of the immune system in chicks. 3. In hatchlings, basal expression of immune genes (AvBD-1, PSEN-1, and IL-6) was evaluated in the duodenum using real-time PCR. The expression of these genes was measured weekly for three weeks after hatching, 3 h after intraperitoneal lipopolysaccharide (LPS) injection. At these times, the heterophil/lymphocyte ratio (He/Ly) was evaluated on blood smears, plasma immunoglobulin Y (IgY) concentrations by ELISA and IL-6 gene expression in the spleen by real-time PCR were determined. 4. During development, the He/Ly ratio and plasma IgY concentration were not significantly influenced by the light quality during incubation. Red light increased gene expression of AvBD-1 in hatchlings and IL-6 in two-week-old chickens compared to birds incubated under blue light. The expression of IL-6 after LPS stimulation increased in an age-dependent manner, both in the duodenum and the spleen, reflecting the maturation of the immune system. 5. The results suggested that red light may increase the local immune response in the gut immediately after hatching, but this effect was not apparent during later development.